An Adaptive Algorithm of Local dimming for Liquid Crystal Displays - Xiaobing Zhang; Xin Liu; Bo Liu; Jianghong Han; Huaxia Wu (Institute of Advanced Engineering and Science, 2012)
The local dimming backlight technique enables liquid crystal display to present images with high contrast ratio and low power consumption. Considering that it is more important to make sure a high quality of the displayed image when reducing the power consumption, therefore, in this paper the new algorithm chooses RPSNR (the peak signal-to-noise ratio) =30 as the lowest standard to guarantee the quality of image. RPSNR =30 could provide a value that the maximum distortion of the image can be accepted, then, we substitute the maximum gray level of each region into the formula to judge whether satisfy the flow chart. If the value do not meet the condition, we decrease it one by one until find the right value. Finally, we take the luminance of the right value as backlight luminance. Meanwhile, a method is also proposed in this paper to simplify the calculation time. Successive searches will be made on the basis of the n (ranging from 0.1 to 1) times of the maximum luminance, and stop when RPSNR>=30. However, in order to guarantee the quality of the image, the 0.7 times of the maximum luminance is used as the minimum backlight luminance. In the end, we only choose 0.7, 0.8 and 0.9 times of the maximum luminance as backlight luminance. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1602